2013
DOI: 10.7150/jgen.3996
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Gene Atlas in Mammals

Abstract: Obesity in humans has increased at an alarming rate over the past two decades and has become one of the leading public health problems worldwide. Studies have revealed a large number of genes/markers that are associated with obesity and/or obesity-related phenotypes, indicating an urgent need to develop a central database for helping the community understand the genetic complexity of obesity. In the present study, we collected a total of 1,736 obesity associated loci and created a freely available obesity data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 37 publications
0
50
0
Order By: Relevance
“…We also recovered genes corresponding to economically important traits that are valuable for future functional analyses and improvements of pig as an important livestock species, such as genes related to pork production (74 of 1515 fat deposition genes [Kunej et al 2013], or 4.88%) and disease resistance (76 of 1517 genes annotated with the GO: 0002376; immune system process, or 5.01%) (Supplemental Table S19). Typical examples are shown in Supplemental Figure S40.…”
Section: Recovery Of Missing Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…We also recovered genes corresponding to economically important traits that are valuable for future functional analyses and improvements of pig as an important livestock species, such as genes related to pork production (74 of 1515 fat deposition genes [Kunej et al 2013], or 4.88%) and disease resistance (76 of 1517 genes annotated with the GO: 0002376; immune system process, or 5.01%) (Supplemental Table S19). Typical examples are shown in Supplemental Figure S40.…”
Section: Recovery Of Missing Genesmentioning
confidence: 99%
“…3B; Supplemental Fig. S25A; Kunej et al 2013), including factors involved in the regulation of feed intake and energy homeostasis (CEP120, GABRA2, NPPA, NPY1R, and NYP5R), lipid metabolism (ABCC4, ANGPT2, LRPAP1, and PRKAG2), and indicators of obesity-induced hypertension, inflammatory signaling, and insulin resistance (ADD1, HSPD1, MMP2, PIK3R4, RAE1, and TBCA) (Supplemental Table S13). In contrast to highly inbred European pigs that have undergone selection for lean growth (high protein and low fat content; lean meat percentage of the carcass ranging between 63%-73%) as a response to demands for reduced calorie intake in modern society, Chinese pigs have been selected for extreme fatness all along (typical lean meat percentage is under 45%) (Supplemental Fig.…”
Section: Signatures Of Diversifying Selection In Pig Breedsmentioning
confidence: 99%
“…The same principle applies to humans: those with VLDLR gene mutations have lower body weight compared with the control group (Boycott et al, 2005;Crawford et al, 2008). Therefore, VLDLR were confirmed to be associated with body weight and obesity in humans and mice (Brockmann et al, 1998;Kunej et al, 2012;Clemente-Postigo et al, 2011). In overweight humans, it was observed that VLDLR were significantly upregulated and their expression levels were probably closely linked to the molecular markers of obesity phenotype (Kim et al, 2012).…”
Section: Introductionmentioning
confidence: 82%
“…Studies using VLDLR-deficient and transgenic mice have provided compelling evidence that VLDLR does indeed play a role in VLDL-triglyceride metabolism, and that it is important for triglyceride storage in the adipocyte . In human and mouse, VLDLR were confirmed to be correlated to body weight and adiposity (Brockmann et al 1998;Rankinen et al 2006;Clemente-Postigo et al 2011;Kunej et al 2012). Significant upregulations of ARG1 (Arginase 1) and VLDLR were observed in the overweight condition and their expression levels are likely to be closely linked to the phenotypic biomarkers for adipose deposition and obesity (disturbed lipid profiles and endothelial dysfunction) (Kim et al 2012).…”
Section: Introductionmentioning
confidence: 99%